Gastrointestinal parasites in wild and exotic animals from a Zoobotanical Park in Northeast of Brazil (Research, Society and Development, 2021)
One of the obstacles for ex situ conservation of wild and exotic animals are the diseases that affect them in captivity and, among them, the endoparasitoses, which are very frequent. The objective of this study is to report the occurrence of endoparasites in the fecal samples of animals from the Arruda Câmara Zoobotanical Park, at João Pessoa, Paraiba State, Brazil, as well as to identify significant statistical differences between the percentages of each parasite species found. To this end, 66 fecal samples were obtained from 50 species of animals including mammals, birds, and reptiles. Statistical differences between the percentages of each parasite species were obtained using the binomial test at 5% significance level. A total of 54.5% (36/66) of the fecal samples were positive (p=0.539), among which 80.5% (29/36) presented nematodes, followed by cestodes 19.4% (07/36), protozoans 13.9% (05/36), and mites 16.7% (06/36). This study reports for the first time the association of Balantidium sp. with Tapirus terrestris, Bertiella sp. with Alouatta caraya, Hymenolepis spp., and Aspiculuris spp. as spurious parasites in reptiles; and Entamoeba coli and Eimeria spp. with Iguana iguana in the northeastern part of the country. This study provides knowledge about some of the endoparasites that may occur in zoos in the northeastern region of the country, as well as in expanding the ecological data on wild and exotic animals.